The Impact Of Lullaby Music Therapy On Physiological Stability In Low Birth Weight Infants - Yunita Liana; Ersita Ersita; Meta Nurbaiti; Romliyadi Romliyadi; Kardewi Kardewi; Oktia Putri (Jurnal Ners, 2025)
Physiological instability, which encompasses fluctuations in body temperature, heart rate, respiration rate, and oxygen saturation, is a substantial concern for low birth weight infants (LBWI). Lullaby music therapy is a non-pharmacological treatment that assists in the stabilization of the physiological condition of neonates with extremely low birth weight. This study aimed to investigate the physiological status of low-birth-weight neonates in response to lullaby music therapy. This study was designed as a quasi-experimental pretest-posttest study that involved 20 low-birth-weight infants. A lullaby music treatment was administered for 45 minutes on each of the three consecutive days, with a frequency of 60-70 dB. The intervention was implemented through a speaker that was situated in close proximity to the infant's feet within the incubator. Before and during the treatment, the physiological parameters assessed were body temperature, heart rate, respiration rate, and oxygen saturation. The Wilcoxon signed-rank test was employed to analyze the data. Significant discrepancies were observed between pre- and post-therapy measurements for all parameters, including body temperature (Z = -2.591; p = 0.010), heart rate (Z = -2.765; p = 0.006), respiratory rate (Z = -3.930; p < 0.001), and oxygen saturation (Z = -3.934; p < 0.001). In hospital environments, lullaby music treatment has the potential to serve as an effective supportive intervention in stabilizing the physiological state of neonates with Low Birth Weight (LBWI) and significantly enhances their physiological condition.